Kenakalan Remaja Ditinjau dari Kasih Sayang Orang Tua dan Pengaruh Teman Sebaya pada Siswa SMP - Nathasya Adifa Pramesthi; Mohammad Khasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the relationship between parental love and peer influence on juvenile delinquency at SMP Negeri 2 Pucakwangi. The method used in this research is quantitative with regression analysis techniques. The results of the study show that there is no very significant relationship between parental love and the influence of peers on juvenile delinquency, with an effective contribution of 19.1%. This means that these factors only influence juvenile delinquency in a small percentage, while the other 80.9% are influenced by other factors not examined in this study. Internal factors, such as lack of attention and love from parents, as well as external factors, such as the social environment, play a role in shaping adolescent behavior. Therefore, a holistic approach is needed from families, schools and communities in preventing and dealing with juvenile delinquency.